ANALISIS DESAIN PEMBELAJARAN PKN DI SD/MI KELAS TINGGI - Rora Rizky Wandini; Siti Maghfhirah; Ahmad Tarmizi Hasibuan (MAGISTRA: Media Pengembangan Ilmu Pendidikan Dasar dan Keislaman, 2021)
Abstract Citizenship education teaches students to know everything that includes themselves and their country. At the end, students will be asked to apply the values of this subject. For example, on theme national identity which means identity of Indonesian nation, namely Pancasila. By implementing Pancasila in everyday life, it means that the students have shown their national identity. However, in this case, the effort to apply PKn in daily life is not an easy thing, therefore it is necessary for students to prepare PKn learning designs so the students enjoy the lesson and make it easier for them to apply the content of PKn subject values. This study uses the literature study method. The author collects various data sources as reference material to complete this paper. The results of the study, it can be concluded that PKn Learning Design in Higher Class of SD/MI, 1) the use visual media, 2) the method of question and answer, 3) the use of Picture Media, 4) the use of Multimedia, 5) an active, creative, effective, and effective learning approach. fun, 6) Horay course review model by using power point, 7) the use of Learning Media, 8) the use of Discussion Method, 9) Active learning strategy of crossword puzzle type. Keywords: Learning Design, PKn, Higher Class